Some Difference Double Sequences Spaces with Respect to Double Orlicz Function - Hussain Battor, Ali; Abdulameer Kadhim, Dhuha; Hayder Hasan, Zainab (International Journal of Engineering and Technology, 2018)
This work concerned with studying of new difference double sequence spaces concerning with lacunary sequences with respect to double Orlicz function. Moreover, from this work we proved some inclusion relations involving these spaces.